Pengaruh Asal-Usul Bahasa dalam Membentuk Gaya Berbicara - Nabila Regina Putri; Arief Diwi Al Majid; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Language origin plays an essential role in shaping an individual’s speaking style because the first language acquired in childhood forms fundamental phonological, syntactic, and semantic patterns that persist into adulthood. The central issue discussed in this study is that differences among Indonesia’s regional languages create noticeable variations in accents, intonation, vocabulary choices, and sentence structures when speakers use Indonesian. This study aims to describe how the mother tongue influences speaking style and to explain the linguistic aspects underlying these differences. Using a library research approach, this study gathers and analyzes scientific references such as books, academic articles, and research journals related to language origin and speaking behavior. The analysis shows that the influence of the first language appears in several aspects, including phonological features such as stress patterns, vowel length, consonant articulation, and speech rhythm; syntactic habits that shape tendencies to construct direct, concise sentences or longer, layered structures; and lexical preferences aligned with the semantic patterns of the regional language. These influences remain evident even when Indonesian is used as a unifying national language, especially in multilingual interactions where speakers from different linguistic backgrounds communicate. Overall, language origin significantly contributes to the diversity of speaking styles in multilingual societies and affects how messages are delivered and interpreted in everyday communication.